Implementasi Kebijakan Pengelolaan Sampah Di Tempat Pemrosesan Akhir - Ghazi Hashim; Feriz Ghazanfer (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
The importance of news for the community was also explained by Sumadiria that news is the fastest report on the latest facts and ideas that are correct, interesting or important to the wider community, through periodic media such as newspapers, radio, television, or internet online media (2005 p. 64). This means that news is information that can be said to be important and that most people want to know.